A novel approach for efficient fatigue based shape optimisation of large scale finite element analysis models. (2017) - Ozturk, Umud Esat
This paper presents a novel approach for efficient fatigue based shape optimisation of large scale finite element analysis models using the engine block connection to the engine mount bracket as an example. It is not practical to perform a shape optimisation study for such problems using standard analysis and optimisation procedures owing to the complexity of the multi-body dynamics and finite element analysis models needed. The developed procedure was successfully employed to calculate the boundary conditions using nonlinear finite element analysis and to perform the fatigue based shape optimisation using the pre-defined shapes as design variables. The modelling and computational efforts of the proposed method are within the practical limits of the product development process. The developed methodology can also be applied to other vehicle components where shape optimisation study is not found feasible owing to the complexity of the interacting sub-systems.